What should we code in health records with the International Classification of Primary Care? - Pinto, Daniel (2014)
In Portugal, family physicians use the International Classification of Primary Care (ICPC) for coding in their electronic health records. However, questions about the use of the classification in daily practice are common. This text aims to clarify what should be coded in health records. ICPC allows the coding of reasons for encounter, health problems, and the process of care. Users should avoid confusion of these terms with the headings “subjective”, “assessment” and “plan” in follow-up notes of the problem-oriented medical record. In daily practice, most users should limit themselves to the coding of health problems. Family physicians should focus on coding the main problems of the patient and maintaining a list of all problems